2012
DOI: 10.1517/14728222.2012.719879
|View full text |Cite
|
Sign up to set email alerts
|

DISC1 as a therapeutic target for mental illnesses

Abstract: Introduction Many genetic studies have indicated that DISC1 is not merely “disrupted-in-schizophrenia,” but is more generally implicated in various brain dysfunctions associated with aberrant neurodevelopment and intracellular signaling pathways. Thus, the DISC1 gene is mildly associated with a variety of brain disorders, including schizophrenia, mood disorders, and autism. This novel concept fits with the results from biological studies of DISC1, which include cell and animal models. Areas covered We review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 113 publications
(138 reference statements)
1
35
0
Order By: Relevance
“…14 To dissect the functional protein domains in the larval neurons, we overexpressed a series of mutant DISC1 proteins (Fig. 1C) and analyzed their localization (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 To dissect the functional protein domains in the larval neurons, we overexpressed a series of mutant DISC1 proteins (Fig. 1C) and analyzed their localization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…14 In this study, we expressed human DISC1 in developing fruit fly neurons, and performed behavioral and neurodevelopmental studies in living organisms (summarized in Table 1). We have shown that overexpression of DISC1 causes associative memory defects in fruit fly larvae.…”
Section: Discussionmentioning
confidence: 99%
“…DISC1 was initially identified when a loss-of-function translocation in the gene was discovered in Scottish families who suffered from mental disease (2731). Subsequently, DISC1 has been implicated in bipolar disorder (32), MDD (33), and autism (34).…”
Section: Discussionmentioning
confidence: 99%
“…These interacting proteins include nuclear distribution protein NudE-like 1 (NDEL1), platelet-activating factor acetylhydrolase 1B subunit alpha (PAFAH1B1, a.k.a. LIS1), Bardet-Biedl syndrome 4 (BBS4), Girdin/KIAA1212, phosphodiesterase 4 (PDE4), Kalirin7, TRAF2- and NCK-interacting kinase (TNIK), and glycogen synthase kinase 3β (GSK3β) (Brandon and Sawa, 2011; Hikida et al, 2012). Recent studies have identified even more interactors of DISC1, such as dopamine D2 receptors (D2R) (Su et al, 2014) and mRNA for inositol-1,4,5-trisphosphate receptor type 1 (ITPR1) (Tsuboi et al, 2015).…”
Section: Disc1 As a Scaffold Protein In Neurodevelopment And Synapticmentioning
confidence: 99%